2019
DOI: 10.1002/eap.1889
|View full text |Cite
|
Sign up to set email alerts
|

Increased reliance of stream macroinvertebrates on terrestrial food sources linked to forest management intensity

Abstract: Our understanding of how forest management practices affect the relative importance of autochthonous vs. allochthonous resource use by headwater stream food webs is relatively poor. To address this, we used stable isotope (C, N, and H) analyses of food sources and macroinvertebrates from 15 streams in New Brunswick (Canada) and assessed how different catchment conditions arising from the gradient in forest management intensity affect the contribution of autochthonous resources to these food webs. Aquatic prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 83 publications
(194 reference statements)
2
14
2
Order By: Relevance
“…Though increases in autochthonous contributions to consumer diets occur after forest harvesting, likely due to increased delivery of nutrients and light to streams stimulating aquatic primary production or to stream-side vegetation removal limiting the subsidies of terrestrial detritus (Göthe et al, 2009), this was not observed in the present study or in other harvested headwater systems where decreased reliance on algae was found, likely from the greater inputs of terrestrial organic matter from harvesting residues and sediment deposition and heterotrophic biofilms at these sites (Erdozain et al, 2019;Göthe et al, 2009;Jonsson et al, 2018). The lack of increase in autochthony in consumer diets at the harvested sites was noted despite greater concentrations of total dissolved nitrogen (Supporting Table S1) and may be due to the presence of riparian buffers.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Though increases in autochthonous contributions to consumer diets occur after forest harvesting, likely due to increased delivery of nutrients and light to streams stimulating aquatic primary production or to stream-side vegetation removal limiting the subsidies of terrestrial detritus (Göthe et al, 2009), this was not observed in the present study or in other harvested headwater systems where decreased reliance on algae was found, likely from the greater inputs of terrestrial organic matter from harvesting residues and sediment deposition and heterotrophic biofilms at these sites (Erdozain et al, 2019;Göthe et al, 2009;Jonsson et al, 2018). The lack of increase in autochthony in consumer diets at the harvested sites was noted despite greater concentrations of total dissolved nitrogen (Supporting Table S1) and may be due to the presence of riparian buffers.…”
Section: Discussioncontrasting
confidence: 60%
“…where ω is the per-trophic level contribution of dietary water to consumers and τ is the trophic level (τ = 1 for primary consumers, including hydropsychids). A ω of 0.20 was assumed based on previous studies (Erdozain et al, 2019;Solomon et al, 2009;Wang et al, 2009;Wilkinson et al, 2015). The relative contribution of aquatic organic matter to the diet of hydropsychids (percentage of algae in diet) was estimated using a two-source mixing model, according to Equation 3:…”
Section: Autochthony Of Primary Consumersmentioning
confidence: 99%
See 1 more Smart Citation
“…Such sources could be from forestry or other land use activities outside of Fundy National Park that have changed the isotopic composition of the aquatic food web. Forest harvesting impacts the stable isotope values of basal resources and subsequent trophic levels (Richardson 2008) by increasing the delivery of terrestrial organic and inorganic materials to aquatic systems and shifting the reliance of biota to more terrestrial carbon sources (Erdozain et al 2019). In addition, there is variability in nature that we captured but cannot fully explain.…”
Section: R a F Tmentioning
confidence: 99%
“…While relatively narrow buffer strip may (or may not; Vuori & Joensuu 1996) protect the stream from sedimentation, few rows of trees unlikely provide effective protection for natural values on the riparian zone. Furthermore, forestryassociated ground disturbance can affect aquatic food webs despite buffers (Erdozain et al 2019). If the aim is to develop a dispersal corridor, then the buffer zone should be long and continuous, but not necessarily wide (see Gundersen 2010).…”
Section: Management Of Riparian Forests and Protection Of Streamsmentioning
confidence: 99%